Integrasi Teknologi dalam Model Hannafin and Peck: Transformasi Pembelajaran PAI yang Dinamis - Unil_Ilma, Miska; Safwandy_Nugraha, Mulyawan (Khulasah : Islamic Studies Journal, 2024)
Technology and information in learning have a vital role. With technology and information, learning will be more varied and in line with the demands of the times. One learning design model that can integrate technology with learning is the Hannafin and Peck model. This research aims to determine the application of technology using the Hannafin and Peck model in PAI learning. This research uses a qualitative approach with a case study type that takes place at SMPN 1 Serangpanjang Subang. In theory, the Hannafin and Pack model is not known to PAI teachers at SMPN 1 Serangpanjang. Still, in practice, PAI teachers there have implemented technology integration with the Hannafin and Pack model.